2019
DOI: 10.4093/dmj.2019.0043
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Bile Acid Signaling in Diabetes: From Pathophysiology to Therapeutic Targets

Abstract: Diabetes and obesity have reached an epidemic status worldwide. Diabetes increases the risk for cardiovascular disease and non-alcoholic fatty liver disease. Primary bile acids are synthesized in hepatocytes and are transformed to secondary bile acids in the intestine by gut bacteria. Bile acids are nutrient sensors and metabolic integrators that regulate lipid, glucose, and energy homeostasis by activating nuclear farnesoid X receptor and membrane Takeda G protein-coupled receptor 5. Bile acids control gut ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 135 publications
2
67
0
Order By: Relevance
“…DCA, transformed by rectal taurocholate (TCA), increases GLP-1 secretion and insulin, leading to decreased serum glucose by activating intestinal bile acid receptors FXR and TGR5 [94,95]. Although UDCA is not used for T2DM directly, it has been used to treat obese patients [96]. Short-term UDCA administration activates FXR to stimulate bile acid and cholesterol synthesis, while circulation of FGF19 decreases.…”
Section: Bile Acid-based Therapy For T2dmmentioning
confidence: 99%
“…DCA, transformed by rectal taurocholate (TCA), increases GLP-1 secretion and insulin, leading to decreased serum glucose by activating intestinal bile acid receptors FXR and TGR5 [94,95]. Although UDCA is not used for T2DM directly, it has been used to treat obese patients [96]. Short-term UDCA administration activates FXR to stimulate bile acid and cholesterol synthesis, while circulation of FGF19 decreases.…”
Section: Bile Acid-based Therapy For T2dmmentioning
confidence: 99%
“…NAFLD is currently the most common cause of chronic liver disease globally, and its reported prevalence in the adult population is 20-30%; however, the prevalence can increases up to 70-90% in obese or diabetic patients [1,2]. NAFLD was previously considered an intra-hepatic phenotype of metabolic syndrome; however, it has since been revealed that NAFLD itself is an independent risk factor for various chronic 4 diseases such as cardiovascular disease (CVD) [3], hypertension [4], diabetes [5,6], and chronic kidney disease [7]. Additionally, because CVD is the most common cause of death among NAFLD patients, studies of the relationship between NAFLD and CVD and underlying mechanisms have been actively conducted [8].…”
Section: Introductionmentioning
confidence: 99%
“…This could explain why AA was identified as one of the top predictors of DM in our study. Alterations in GCDCA, amongst other bile acids, was previously shown to trigger diabetes [ 43 ], which could also explain why it appeared as one of the top predictors of DM in our study (Table 4 ). When…”
Section: Discussionmentioning
confidence: 54%